EXPLORING THE LINK BETWEEN DIET AND MENTAL HEALTH: A REVIEW OF RECENT FINDINGS. - ‏Amirah Ayed Alshammari, ‏Saud Marshad Alshammary, Saidan Hadaisan Alshammari, Ali Mohammed Khdier Alenazi, Faisal Khalid Naji Alshammari, Ahmad Noman Alsaleh (Chelonian Research Foundation, 2022)
Scientific research is increasingly demonstrating the critical role that nutrients play in maintaining brain health and cognitive performance. This thorough analysis delves into the complex interplay between different nutrients and mental health, highlighting their significant effects on neurotransmitter function, neuroplasticity, and mood regulation. Both micronutrients like vitamins and minerals and macronutrients like fatty acids, proteins, and carbs have a major impact on emotional stability and cognitive function. Polyphenols, B-group vitamins, and omega-3 fatty acids are important components of neuroprotection since they have been shown to improve neurotransmitter regulation and synaptic plasticity. Moreover, the gut microbiota becomes an important mediator, generating bioactive substances that affect oxidative stress and inflammation, two factors linked to mental health issues. The interplay among mental health, inflammation, and oxidative stress highlights the significance of dietary treatments in enhancing brain function. Research indicates that anti-inflammatory and antioxidant-rich plant-based diets may be beneficial in halting cognitive aging and lowering the incidence of neurodegenerative illnesses. On the other hand, diets heavy in sugar, processed foods, and bad fats exacerbate cognitive decline by causing systemic inflammation. To sum up, the combination of lifestyle changes and a well-balanced, nutrient-rich diet is essential for promoting brain health and reducing the likelihood of mental health issues. This study emphasizes how important nutrition is for maintaining cognitive function and how dietary treatments might improve mental health over the life span.